Global Risk Management – A Necessity in a World of Vulnerabilities and of ECO-Economy and BIO -ECO-Economy Needed by ECO-SANO-Genesis - Gurgu, Elena (Journal of Economic Development, Environment and People, 2015)
Abstract. The Vision of the Eco-Bio-Economy is to sustain development of the humankind welfare in all forms, through an economy of future dedicated to human life through the rational use of the environmental resources. The present work attempts to discuss the issues that humanity faces at the beginning of a new global economic paradigm. The minimum point of the financial crisis started in 2008 meets the final years of the decline phase of the long term global economic cycle. The feeling is one of lack of vision on the part of Governments, of improvisation, of passive reaction, such as seeing and doing. One feels that the economic context is worn out , dysfunctional because of deep recovery problems. The perception, not far from the taugh reality, is that of a national competition meant to minimize losses caused by the financial crisis and to use beggar thy neighbor types of policies, similar to finding the way out of the crisis on the expense of others.